Gospel Images of Jesus Christ in Church Tradition and in Biblical Scholarship Fifth International East-West Symposium of New Testament Scholars, Minsk, September 2 to 9, 2010 - Niebuhr, Karl-Wilhelm; Karakolis, Christos; Rogalsky, Sviatoslav; Rogalsky, Sviatoslav (Mohr Siebeck, 2012)
Die Jesus-Christus-Darstellung der Evangelien in den kirchlichen Traditionen und in der Bibelwissenschaft. Fünfte internationale orthodox-westliche Exegetenkonferenz, Minsk, 2. bis 9. September 2010.
PublicationDate: 20120724
Keywords: Hermeneutics -- Biblical Studies -- black listin -- Jesus Research -- Ecumenical Theology -- Neues Testament -- Array